Caro, Isaac Movimientos Religiosos Islámicos en el Escenario Internacional: Implicancias para las Américas, Santiago, USACH/IDEA, 2001 (204 páginas). ISBN 35602 00539 0135 - Kinglow, Flor Elisa (Estudios Avanzados, 2011)
Caro, Isaac Movimientos Religiosos Islámicos en el Escenario Internacional: Implicancias para las Américas, Santiago, USACH/IDEA, 2001 (204 páginas). ISBN 35602 00539 0135